2011
DOI: 10.1016/j.jcrs.2010.12.058
|View full text |Cite|
|
Sign up to set email alerts
|

Corneal asphericity and spherical aberration after refractive surgery

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
57
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 26 publications
7
57
1
Order By: Relevance
“…The shape of the cornea is more natural after tissue addition compared with tissue subtraction, which does not lead to significant induction of HOAs 21. The total HOAs after FILI remain within normal acceptable values and may be better than hyperopic LASIK/photorefractive keratectomy 22,23.…”
Section: Discussionmentioning
confidence: 99%
“…The shape of the cornea is more natural after tissue addition compared with tissue subtraction, which does not lead to significant induction of HOAs 21. The total HOAs after FILI remain within normal acceptable values and may be better than hyperopic LASIK/photorefractive keratectomy 22,23.…”
Section: Discussionmentioning
confidence: 99%
“…After myopic LASIK, the corneal asphericity becomes oblate. [23][24][25] With increasing oblateness, the difference in keratometry between the measured portion and the corneal center increases and leads to a hyperopic shift in the postoperative refraction. In the same manner, the deviation from spherical in the anterior corneal profile leads to increases in the postoperative refractive error.…”
Section: Discussionmentioning
confidence: 99%
“…10 Clearly, greater refractive correction requires greater corneal reshaping and therefore necessitates a greater net DQ. 11 However, DQ depends on more than just the amount of refractive correction accomplished. An increased change in asphericity can be caused by variable application of laser fluence with treatment depth, stromal and epithelial remodeling after surgery, and variable laser efficiency with the cosine effect and oblique incidence of laser energy.…”
mentioning
confidence: 99%
“…[13][14][15] It has been suggested that both lasers have a similar effect on the final HOA. 11,16,17 However, on review of the literature, no studies examining the effect of lasers on the Q value for PRK were found.…”
mentioning
confidence: 99%